Rhodobacteraceae are the key members of the microbial community of the initial biofilm formed in Eastern Mediterranean coastal seawater. Issue 2 (18th April 2013) - Elifantz, Hila; Horn, Gilad; Ayon, Meir; Cohen, Yehuda; Minz, Dror
Abstract: The formation of biofilms and biofouling is a common feature in aquatic environments. The aim of this study was to identify the primary colonizers of biofilm formed in Eastern Mediterranean Coastal water at different seasons and follow early dynamics of biofilm community development. Pre‐treated coastal seawater and biofilm samples were collected from six different sampling events of 2 weeks' duration each during 1 year. The microbial community composition and specific abundance were estimated by 16S rRNA gene clone libraries and fluorescence in situ hybridization–confocal laser scanning microscopy (FISH‐CLSM), respectively. The biofilm formed over the course of the year was fairly consistent in terms of community composition and overall abundance with the exception of spring season. Alphaproteobacteria (30–70% of total bacteria), in particular Rhodobacteraceae, were the dominant bacteria in the biofilm, regardless of season, followed by Bacteroidetes (5–35%) and Gammaproteobacteria (6–35%). There was a decrease in relative abundance of Alphaproteobacteria and an increase in the abundance of Bacteroidetes between the initial and 2‐week‐old biofilm. This observation may aid man‐made facilities that have to deal with biofilm formation and help the development of appropriate strategies to control those biofilms.